2021
DOI: 10.3389/frvir.2021.706653
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons Between First Person Point-of-View 180° Video Virtual Reality Head-Mounted Display and 3D Video Computer Display in Teaching Undergraduate Neuroscience Students Stereotaxic Surgeries

Abstract: Introduction: Students interested in neuroscience surgical applications learn about stereotaxic surgery mostly through textbooks that introduce the concepts but lack sufficient details to provide students with applied learning skills related to biomedical research. The present study employed a novel pedagogical approach which used an immersive virtual reality (VR) alternative to teach students stereotaxic surgery procedures through the point of view (POV) of the neuroscientist conducting the research procedure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…31 Others have developed open-access VR anatomical programs for students to use for home education, especially during the COVID-19 pandemic, when professional medical and veterinary colleges and universities were unable to offer conventional lessons. 29,30,32 In the field of laboratory animal science, only Tang et al. have reported the development and implementation of ViSi as an animal-handling training method for biomedical science undergraduates.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…31 Others have developed open-access VR anatomical programs for students to use for home education, especially during the COVID-19 pandemic, when professional medical and veterinary colleges and universities were unable to offer conventional lessons. 29,30,32 In the field of laboratory animal science, only Tang et al. have reported the development and implementation of ViSi as an animal-handling training method for biomedical science undergraduates.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that use of 180° VR videos might enhance the learning outcomes of undergraduate students studying stereotaxic surgery, and that this technology could help prevent exacerbation of the learning gap created by the COVID-19 pandemic. 32…”
Section: Discussionmentioning
confidence: 99%